Exploring Verbal and Non-Verbal Expressions of ESP Undergraduates’ own Voices and Identities - García-Pinar, Aránzazu (International Journal of English Studies, 2022)
Given the ubiquity of digital technologies in all sorts of academic contexts, it is generally assumed that many undergraduates’ writing tasks will include verbal and visual modes these days. The interweaving of different modes allows students to express different multidisciplinary and individual identities while they become agents and designers of different L2 learning tasks. Using an interpretative qualitative approach, the present study explores the authorial voices and stance that four engineering undergraduates enacted in their presentation slides for an in-class oral presentation. Data sources included screen capture, classroom observation, and interview transcripts. Findings revealed that behind students’ collaborative compositional processes there are complex multimodal decisions that help them express their identities and enhance their engagement in the L2. Students perceived their presentation slides as artefacts to accommodate their audience and as means through which they were able to represent themselves as agents and designers of the discipline of engineering. Based on the results, this study highlights different pedagogical implications and ideas for English for specific purposes (ESP) contexts.